Technical Perspective When the Adversary Is Your Friend. - Efros, Alexei A.; Hertzmann, Aaron (Communications of the ACM, 2020)
An introduction to an article in the journal about the topic of Generative Adversarial Networks (GANs) and how GAN-based models may impact society on political and cultural levels is presented.